The complete plastid genome of Bauhinia variegata L. var. variegata (Leguminosae) - Shiran Gu; Yong Chen; Danjing Zheng; Shiyuan Meng; Tieyao Tu (Mitochondrial DNA. Part B. Resources, 2020)
Bauhinia variegata L. var. variegata is a popular ornamental tree in the tropical and subtropical region. We herein report and characterize the complete plastid genome of B. variegata var. variegata in an effort to provide genomic resources for genetic utilization. The complete plastome is 155,415 bp in length and contains the typical quadripartite structure, including two inverted repeat (IR) regions of 25,549 bp, a large single-copy (LSC) region of 86,110 bp and a small single-copy (SSC) region of 18,207 bp. 130 genes are annotated, including 85 protein-coding genes, 37 transfer RNA genes, and four unique ribosomal RNA genes. The phylogenetic analysis based on the plastomes from B. variegata var. variegata and 12 previously reported species of Cercidoideae suggested a sister-relationship between B. variegata var. variegata and B. × blakeana with a strong bootstrap value.